2014
DOI: 10.3109/03630269.2014.930044
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Indices and Formulas Used in Differentiation of β-Thalassemia Trait from Iron Deficiency in Thai School Children

Abstract: Red cell indices and formulas have been established as simple, fast, and inexpensive means for discrimination between the β-thalassemia (β-thal) trait and iron deficiency. However, there were no reports of the diagnostic reliability of different red cell indices and formulas in discrimination of β-thal trait from iron deficiency in the Thai population. The aim of this study was to examine the diagnostic accuracy of five red cell indices [red blood cell (RBC) count, mean corpuscular volume (MCV), mean corpuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 17 publications
3
26
1
2
Order By: Relevance
“…In the present study, RBC counts of b-thal trait were significantly higher than those of iron deficiency (5.7 vs. 4.3 Â 10 12 /L, p50.001) and was consistent with the previous studies (9)(10)(11)23). The RDW of the former was significantly lower than those of the latter (14.9 vs. 16.2%, p50.001).…”
Section: Parameterssupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, RBC counts of b-thal trait were significantly higher than those of iron deficiency (5.7 vs. 4.3 Â 10 12 /L, p50.001) and was consistent with the previous studies (9)(10)(11)23). The RDW of the former was significantly lower than those of the latter (14.9 vs. 16.2%, p50.001).…”
Section: Parameterssupporting
confidence: 93%
“…However, it had a low specificity (66.70%) in detection of iron deficiency. The previous study in Thai school children, aged 8-14 years, showed that the Sirdah and Srivastava formulas provided the highest reliabilities in initial differentiation of b-thal trait from iron deficiency (10). Contrary to the present study, it showed that RDW/RBC was a reliable formula for discrimination between b-thal trait and iron deficiency in adult Thai subjects.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations